The Influence of Accounting Conservatism, Earnings Persistence, and Firm Size : Effects on Earnings Response Coefficient in Energy Firm - Mardiaton Mardiaton; Desy Al-Ftryanti; Cut Sri Firman Hastuti; Rimal Maldani; Dian Ariani (Department of Accounting, Faculty of Economics & Business, 2026)
This study investigates the relationships among accounting conservatism, earnings persistence, and firm size, and the Earnings Response Coefficient (ERC) of energy companies listed on the Indonesia Stock Exchange (IDX) during the period 2022–2024. The research aims to: (1) analyze the effect of accounting conservatism on ERC; (2) examine the impact of earnings persistence on ERC; and (3) assess the influence of firm size on ERC. A quantitative approach was employed using secondary data derived from financial reports available on the IDX website, complemented by relevant literature. Panel regression analysis was conducted with EViews 12 software to evaluate the hypotheses. The findings reveal that accounting conservatism has a negative, but statistically insignificant, effect on ERC; earnings persistence has a negative, statistically significant effect on ERC; and firm size has a positive, but statistically insignificant, effect on ERC. These results provide empirical evidence on the determinants of ERC in the Indonesian energy sector, contributing to the literature by highlighting the role of firm-specific characteristics in shaping market responses to earnings information and offering practical insights for investors, regulators, and academics